Positive pole piece, battery and electric device

CN119744454AActive Publication Date: 2025-04-01CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380061208.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-04-13
Publication Date
2025-04-01
Estimated Expiration
2043-04-13

AI Technical Summary

Technical Problem

Existing lithium iron manganese phosphate cathode active materials lead to reduced kinetic performance and low rate performance in secondary batteries, and cannot meet the high energy density, cycle performance and safety performance requirements of power batteries.

Method used

The cathode active material uses a two-layer coating structure. The core is Li1+xMn1-yAyP1-zRzO4. The first coating layer is pyrophosphate MaP2O7 and phosphate XnPO4. The second coating layer is carbon element. By doping specific elements And the design of the coating layer improves the conductivity and structural stability of the material, reduces manganese dissolution and oxygen activity, and enhances the migration ability of lithium ions.

Benefits of technology

It significantly improves the rate performance, cycle performance, low-temperature performance and safety of the battery, enhances the energy density, extends the cycle life of the battery, and reduces the corrosion of active materials by the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119744454A_ABST
    Figure CN119744454A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece, a battery and an electric device. The positive pole piece comprises a first positive active material and a second positive active material; the first positive electrode active material comprises an inner core, a first coating layer coating the inner core and a second coating layer coating the first coating layer; wherein the inner core comprises a compound Li < 1 + x > Mn < 1-y > A < y > P < 1-z > R < z > O < 4 >, the first coating layer comprises pyrophosphate and phosphate, and the second coating layer comprises a carbon element; the second positive electrode active material contains lithium manganese oxide. The battery prepared from the positive pole piece is high in rate capability, good in dynamic performance and low-temperature performance, good in cycle performance and high in safety.
Need to check novelty before this filing date? Find Prior Art

Description

Positive electrode sheet, battery and power-consuming device Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet, a battery, and an electrical device. Background Art

[0002] In recent years, the application of secondary batteries has become increasingly widespread. They are widely used in energy storage systems such as hydropower, thermal, wind, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. This tremendous development of secondary batteries has led to higher requirements for their energy density, cycling performance, and safety. While existing lithium iron manganese phosphate (LiMnFePO4) cathode active materials have their advantages, they can lead to reduced kinetic performance and low rate capability, failing to meet the demands of power batteries.

[0003] Summary of the Invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode plate, a battery and an electrical device. The energy density, rate performance, kinetic performance, low temperature performance, cycle performance and safety of the battery made of the positive electrode active material of the present application are improved.

[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode sheet, comprising a first positive electrode active material and a second positive electrode active material;

[0006] The first positive electrode active material comprises a core, a first coating layer covering the core, and a second coating layer covering the first coating layer; wherein the core comprises a compound Li 1+x Mn 1-y A y P 1-z R z O4, the first coating layer contains pyrophosphate M a P2O7 and Phosphate X n PO4, the second coating layer contains carbon element;

[0007] in,

[0008] A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge;

[0009] R includes one or more elements selected from B, Si, N, and S;

[0010] x is any value in the range of -0.100 to 0.100;

[0011] y is any value in the range of 0.001 to 0.909;

[0012] z is any value in the range of 0.001 to 0.100;

[0013] M and X each independently include one or more elements selected from the group consisting of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al;

[0014] a is greater than 0 and less than or equal to 4;

[0015] n is greater than 0 and less than or equal to 2;

[0016] The second positive electrode active material includes lithium manganese oxide.

[0017] Therefore, the present application obtains a first positive electrode active material by doping a specific element at a specific amount at both the Mn position and the P position of the compound LiMnPO4 and performing a double-layer coating on the surface of the compound, which can greatly reduce the dissolution of transition metals and reduce the oxygen activity on the surface of the particles, promote the migration of lithium ions, improve the conductivity and desolvation performance of the material, improve the rate performance of the battery, improve the cycle performance and high-temperature performance of the battery, and at the same time reduce the corrosion of the electrolyte to the active material.

[0018] In the present application, a first positive electrode active material and a second positive electrode active material, lithium manganese oxide, are mixed and used. The advantages of the two materials complement each other. The particles of the first positive electrode active material are uniformly coated on the surface of the second positive electrode active material, so that the lattice of the second positive electrode active material is relatively independent and the skeleton is stable, which is not easy to collapse during the charging and discharging process of the battery, thereby improving the cycle life of the battery. At the same time, the coating of the first positive electrode active material provides elastic strain for external force impact or shear, effectively solving the safety problem of the second positive electrode active material, thereby improving the energy density of the battery, and making the secondary battery have excellent rate performance, dynamic performance, cycle performance, low temperature performance and safety.

[0019] Unless otherwise specified, in the above chemical formula, when A is two or more elements, the above-mentioned numerical ranges for y are not only defined for the stoichiometric number of each element serving as A, but also for the sum of the stoichiometric numbers of each element serving as A. For example, when A is two or more elements A1, A2, ...An, the stoichiometric numbers y1, y2, ...yn of A1, A2, ...An must each fall within the numerical range defined for y in this application, and the sum of y1, y2, ...yn must also fall within this numerical range. Similarly, for the case where R is two or more elements, the numerical ranges for the stoichiometric numbers of R defined in this application also have the above meanings.

[0020] In any embodiment of the first aspect of the present application, the second positive electrode active material includes LiMn2O4.

[0021] Therefore, the first positive electrode active material is mixed with the above-mentioned second positive electrode active material, which further improves the energy density and rate performance of the battery, and improves the battery's dynamic performance, cycle performance, low temperature performance and safety.

[0022] In any embodiment of the first aspect of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; the positive electrode film layer has a single-layer structure or a multi-layer structure; at least one of the positive electrode film layers with a single-layer structure includes the first positive electrode active material and the second positive electrode active material at the same time, and / or at least one layer of the at least one positive electrode film layer with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material at the same time.

[0023] In any embodiment of the first aspect of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; at least one of the positive electrode film layers has a multi-layer structure, and at least one of the positive electrode film layers with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material in different layers respectively; optionally, at least one of the positive electrode film layers with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material in adjacent layers respectively.

[0024] In any embodiment of the first aspect of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer A and a positive electrode film layer B respectively arranged on two surfaces of the positive electrode current collector; the positive electrode film layer A and the positive electrode film layer B each independently have a single-layer structure or a multi-layer structure; at least one layer of the positive electrode film layer A includes the first positive electrode active material, and at the same time, at least one layer of the positive electrode film layer B includes the second positive electrode active material.

[0025] The present application combines a first positive electrode active material and a second positive electrode active material. The two materials complement each other's advantages, thereby improving the energy density of the battery and enabling the battery to have excellent rate performance, kinetic performance, cycle performance, low temperature performance and safety performance.

[0026] In any embodiment of the first aspect of the present application, the mass ratio of the first positive electrode active material to the second positive electrode active material is 1:7 to 7:1, and can be optionally 1:4 to 4:1. This ensures that the battery has both excellent rate performance and cycle performance, high energy density, excellent kinetic performance and low-temperature performance, reduces interfacial side reactions, and improves battery safety.

[0027] In any embodiment of the first aspect of the present application, in the first positive electrode active material, A includes one or more elements selected from Zn, Fe, Ti, V, Ni, Co, and Mg. Optionally, A includes at least two elements selected from Fe, Ti, V, Ni, Co, and Mg. Selecting the doping element within the above range is beneficial for enhancing the doping effect. On the one hand, it further reduces the lattice change rate, thereby suppressing the dissolution of manganese and reducing the consumption of electrolyte and active lithium. On the other hand, it is also beneficial for further reducing the surface oxygen activity and reducing the interfacial side reactions between the positive electrode active material and the electrolyte, thereby improving the cycle performance and high-temperature storage performance of the battery.

[0028] In any embodiment of the first aspect of the present application, x is any value within the range of -0.100 to 0.006. By selecting the value of x within this range, the kinetic performance of the battery can be improved.

[0029] In any embodiment of the first aspect of the present application, y is any value in the range of 0.001 to 0.500, and can be any value in the range of 0.1 to 0.4. By selecting the value of y within this range, the gram capacity of the first positive electrode active material and the rate performance of the battery can be improved.

[0030] In any embodiment of the first aspect of the present application, M and X each independently include one or more elements of Li and Fe.

[0031] In any embodiment of the first aspect of the present application, the ratio of y to 1-y is selected from 1:10 to 10:1, and may be 1:4 to 1:1. Here, y represents the sum of the stoichiometric ratios of the Mn-doping elements. When the above conditions are met, the energy density and cycle performance of the battery manufactured using the positive electrode sheet can be further improved.

[0032] In any embodiment of the first aspect of the present application, the ratio of z to 1-z is selected from 1:999 to 1:9, and may be 1:499 to 1:249. Here, z represents the sum of the stoichiometric ratios of the P-site doping elements. When the above conditions are met, the energy density and cycle performance of a battery fabricated with the positive electrode sheet can be further improved.

[0033] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the interplanar spacing of the phosphate in the first coating layer is 0.345-0.358 nm, and the angle of the crystal direction (111) is 24.25°-26.45°; and / or, the interplanar spacing of the pyrophosphate in the first coating layer is 0.293-0.326 nm, and the angle of the crystal direction (111) is 26.41°-32.57°.

[0034] When the interplanar spacing and the angle of the crystal orientation (111) of the phosphate and / or pyrophosphate in the first coating layer are within the above range, the impurity phase in the coating layer can be effectively avoided, thereby increasing the specific capacity of the material and improving the cycle performance and rate performance of the battery.

[0035] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the coating amount of the first coating layer is greater than 0 weight % and less than or equal to 7 weight %, and can be optionally 4-5.6 weight %, based on the weight of the core.

[0036] When the coating amount of the first coating layer is within the above range, the dissolution of manganese can be further suppressed, while the transmission of lithium ions can be further promoted, the battery impedance can be reduced, and the dynamic performance of the battery can be improved.

[0037] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the weight ratio of pyrophosphate to phosphate in the first coating layer is 1:3 to 3:1, and can be optionally 1:3 to 1:1.

[0038] The appropriate ratio of pyrophosphate and phosphate is conducive to fully exerting the synergistic effect of the two, inhibiting the dissolution of manganese and reducing battery impedance.

[0039] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the crystallinity of the pyrophosphate and the phosphate are each independently 10% to 100%, and can be optionally 50% to 100%.

[0040] In the first coating layer of the lithium manganese phosphate positive electrode active material of the present application, pyrophosphate and phosphate with a certain degree of crystallinity are beneficial for maintaining the structural stability of the first coating layer and reducing lattice defects. This is beneficial for fully utilizing the pyrophosphate's effect of hindering manganese dissolution. On the other hand, it is also beneficial for the phosphate to reduce the surface impurity lithium content and the valence state of surface oxygen, thereby reducing the interfacial side reactions between the positive electrode material and the electrolyte, reducing the consumption of electrolyte, and improving the cycle performance and safety performance of the secondary battery.

[0041] In any embodiment of the first aspect of the present application, in the first positive electrode active material, the coating amount of the second coating layer is greater than 0 weight % and less than or equal to 6 weight %, and can be optionally 3-5 weight %, based on the weight of the core.

[0042] On the one hand, the carbon-containing layer as the second coating layer can play a "barrier" function, reducing the direct contact between the first positive electrode active material and the electrolyte, thereby reducing the corrosion of the electrolyte on the active material and improving the safety performance of the battery at high temperatures. On the other hand, it has a strong electrical conductivity, which can reduce the internal resistance of the battery, thereby improving the kinetic performance of the secondary battery. However, due to the low gram capacity of the carbon material, when the amount of the second coating layer is too large, the overall gram capacity of the positive electrode active material may be reduced. Therefore, when the coating amount of the second coating layer is within the above range, it can further improve the kinetic performance and safety performance of the secondary battery without sacrificing the gram capacity of the positive electrode active material.

[0043] In any embodiment of the first aspect of the present application, the concentration of Li / Mn antisite defects in the first positive electrode active material is less than or equal to 4%, and can be less than or equal to 2%. In the first positive electrode active material of the present application, the Li / Mn antisite defect refers to the LiMnPO4 lattice. + and Mn 2+ The positions of Li are interchanged. + The transmission channel is a one-dimensional channel, Mn 2+ In Li + It is difficult to migrate in the transmission channel, so the antisite defect Mn 2+ Will hinder Li + By controlling the concentration of Li / Mn antisite defects at a low level, the material's specific capacity and the battery's rate performance can be improved.

[0044] In any embodiment of the first aspect of the present application, the lattice change rate of the first positive electrode active material is less than or equal to 6%, and can be less than or equal to 4%. The lithium insertion and extraction process is a two-phase reaction. The interfacial stress of the two phases is determined by the lattice change rate. The smaller the lattice change rate, the smaller the interfacial stress. + Therefore, reducing the lattice change rate of the core will be beneficial to enhance the Li + transmission capability, thereby improving the rate performance of the secondary battery.

[0045] In any embodiment of the first aspect of the present application, the surface oxygen valence of the first positive electrode active material is less than or equal to -1.88, and can be optionally -1.98 to -1.88. This is because the higher the valence of oxygen in the compound, the stronger its electron-accepting ability, that is, the stronger its oxidizing property. In the first positive electrode active material of the present application, by controlling the surface valence of oxygen at a lower level, the reactivity of the surface of the positive electrode material can be reduced, and the interfacial side reactions between the positive electrode material and the electrolyte can be reduced, thereby improving the cycle performance and high-temperature storage performance of the secondary battery.

[0046] In any embodiment of the first aspect of the present application, the compaction density of the first positive electrode active material under 3 tons (T) is greater than or equal to 2.0 g / cm 3 , can be selected as greater than or equal to 2.2g / cm 3 The higher the compaction density of the first positive electrode active material, that is, the greater the weight of the active material per unit volume, the more conducive it is to improving the volume energy density of the secondary battery.

[0047] In any embodiment of the first aspect of the present application, the sum of the mass of the first positive electrode active material and the second positive electrode active material accounts for 88% to 98.7% of the mass of the positive electrode sheet, further enabling the secondary battery to have excellent rate performance, kinetic performance, cycle performance, and low-temperature performance, and to have a high energy density.

[0048] The second aspect of the present application provides a battery, comprising the positive electrode sheet of the first aspect of the present application.

[0049] A third aspect of the present application provides an electrical device comprising a battery selected from the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application.

[0051] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 1 .

[0052] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0053] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application.

[0054] FIG. 5 is an exploded view of the battery pack shown in FIG. 4 according to an embodiment of the present application.

[0055] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0056] FIG7 is a schematic diagram of a battery structure made of the positive electrode sheet P1 of the present application.

[0057] FIG8 is a schematic diagram of a battery structure made of the positive electrode sheet P2 of the present application.

[0058] FIG9 is a schematic diagram of a battery structure made of the positive electrode sheet P3 of the present application.

[0059] FIG10 is a schematic diagram of a battery structure made of the positive electrode sheet P8 of the present application.

[0060] FIG11 is a schematic diagram of a battery structure made of the positive electrode sheet P10 of the present application.

[0061] FIG12 is a schematic diagram of a battery structure made of the positive electrode sheet P11 of the present application.

[0062] FIG13 is a schematic diagram of a battery structure made of the positive electrode sheet P12 of the present application.

[0063] FIG14 is a schematic diagram of a battery structure made of the positive electrode sheet P17 of the present application.

[0064] FIG15 is a schematic diagram of a battery structure made of the positive electrode sheet P18 of the present application.

[0065] FIG16 is a schematic diagram of a battery structure made of the positive electrode sheet P23 of the present application.

[0066] FIG17 is a schematic diagram of a battery structure made of the positive electrode sheet P24 of the present application.

[0067] FIG18 is a schematic diagram of a battery structure made of the positive electrode sheet P26 of the present application.

[0068] FIG19 is a schematic diagram of a battery structure made of the positive electrode sheet P27 of the present application.

[0069] Description of reference numerals:

[0070] 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly; 11 core; 12 first covering layer; 13 second covering layer. DETAILED DESCRIPTION

[0071] Below, the embodiments of the positive electrode sheet, secondary battery, battery module, battery pack and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0072] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0073] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0074] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0075] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.

[0076] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.

[0077] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A and / or B" means "A, B, or both A and B." More specifically, the condition "A and / or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0078] If not otherwise specified, in this application, the term "at least one" refers to one or more, such as one, two, etc.

[0079] If there is no special explanation, in this application, the median particle size Dv 50 Refers to the particle size corresponding to the cumulative volume distribution percentage of the positive electrode active material reaching 50%. In this application, the median particle size Dv of the positive electrode active material is 50 Laser diffraction particle size analysis can be used for determination, for example, referring to the standard GB / T 19077-2016, using a laser particle size analyzer (such as Malvern Master Size 3000).

[0080] Unless otherwise specified, in this application, the term "coating" refers to a material layer coating the inner core. The material layer may completely or partially coat the inner core. The term "coating" is used for ease of description only and is not intended to limit the present invention. Similarly, the term "thickness of the coating" refers to the thickness of the material layer coating the inner core in the radial direction of the inner core.

[0081] Unless otherwise specified, in this application, the term "source" refers to a compound that is the source of a certain element. As examples, types of "source" include but are not limited to carbonates, sulfates, nitrates, elements, halides, oxides and hydroxides, etc.

[0082] [Secondary battery]

[0083] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged to activate the active materials after discharge and continue to be used.

[0084] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. During the battery's charge and discharge process, active ions (such as lithium ions) are embedded and released back and forth between the positive and negative electrode sheets. The separator is set between the positive and negative electrode sheets, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte between the positive and negative electrode sheets mainly plays the role of conducting active ions.

[0085] [Positive electrode]

[0086] An embodiment of the first aspect of the present application provides a positive electrode sheet, comprising a first positive electrode active material and a second positive electrode active material;

[0087] The first positive electrode active material comprises a core, a first coating layer covering the core, and a second coating layer covering the first coating layer; wherein the core comprises a compound Li 1+x Mn 1-y A y P 1-z R z O4, the first coating layer contains pyrophosphate M a P2O7 and Phosphate X n PO4, the second coating layer contains carbon element;

[0088] in,

[0089] A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge;

[0090] R includes one or more elements selected from B, Si, N, and S;

[0091] x is any value in the range of -0.100 to 0.100;

[0092] y is any value in the range of 0.001 to 0.909;

[0093] z is any value in the range of 0.001 to 0.100;

[0094] M and X each independently include one or more elements selected from the group consisting of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al;

[0095] a is greater than 0 and less than or equal to 4;

[0096] n is greater than 0 and less than or equal to 2;

[0097] The second positive electrode active material includes lithium manganese oxide.

[0098] The first positive electrode active material of the present application is a core-shell structure with two coating layers, wherein the element A doped at the manganese position of the core in the lithium manganese phosphate helps to reduce the lattice change rate of the lithium manganese phosphate during the deintercalation and deintercalation of lithium manganese phosphate, improves the structural stability of the lithium manganese phosphate positive electrode material, greatly reduces the dissolution of manganese and reduces the oxygen activity on the particle surface; the element R doped at the phosphorus position helps to change the difficulty of the Mn-O bond length change, thereby reducing the lithium ion migration barrier, promoting lithium ion migration, and improving the battery's rate performance; the first coating layer of the first positive electrode active material of the present application includes pyrophosphate and phosphate. Since the migration barrier of transition metals in pyrophosphate is high (>1eV), it can effectively inhibit the dissolution of transition metals, and phosphate has excellent lithium ion conductivity and can reduce the surface impurity lithium content; in addition, since the second coating layer is a carbon-containing layer, it can effectively improve the conductivity and desolvation ability. In addition, the "barrier" effect of the second coating layer can further hinder the migration of manganese ions into the electrolyte and reduce the corrosion of the electrolyte on the active material. Therefore, the first positive electrode active material of the present application, by performing specific element doping and surface coating on lithium manganese phosphate, can effectively inhibit the dissolution of Mn during the lithium insertion and extraction process, while promoting the migration of lithium ions, thereby improving the rate performance of the battery cell and enhancing the cycle performance and high-temperature performance of the battery. It should be noted that the positions of the main characteristic peaks of the first positive electrode active material of the present application are basically consistent with those of LiMnPO4 before doping, indicating that the doped lithium manganese phosphate positive electrode active material does not have an impurity phase, and the improvement in battery performance is mainly due to element doping, rather than impurity phases.

[0099] In the present application, a first positive electrode active material and a second positive electrode active material, lithium manganese oxide, are mixed and used. The advantages of the two materials complement each other. The particles of the first positive electrode active material are uniformly coated on the surface of the second positive electrode active material, so that the lattice of the second positive electrode active material is relatively independent and the skeleton is stable, which is not easy to collapse during the charging and discharging process of the battery, thereby improving the cycle life of the battery. At the same time, the coating of the first positive electrode active material provides elastic strain for external force impact or shear, effectively solving the safety problem of the second positive electrode active material, thereby improving the energy density of the battery, and making the secondary battery have excellent rate performance, dynamic performance, cycle performance, low temperature performance and safety.

[0100] Unless otherwise specified, in the above chemical formula, when A is two or more elements, the above-mentioned numerical ranges for y are not only defined for the stoichiometric number of each element serving as A, but also for the sum of the stoichiometric numbers of each element serving as A. For example, when A is two or more elements A1, A2, ...An, the stoichiometric numbers y1, y2, ...yn of A1, A2, ...An must each fall within the numerical range defined for y in this application, and the sum of y1, y2, ...yn must also fall within this numerical range. Similarly, for the case where R is two or more elements, the numerical ranges for the stoichiometric numbers of R defined in this application also have the above meanings.

[0101] In some embodiments of the first aspect of the present application, the second positive electrode active material includes LiMn2O4.

[0102] Therefore, the first positive electrode active material is mixed with the above-mentioned second positive electrode active material, which further improves the energy density and rate performance of the battery, and improves the battery's dynamic performance, cycle performance, low temperature performance and safety.

[0103] In some embodiments of the first aspect of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; the positive electrode film layer has a single-layer structure or a multi-layer structure; at least one of the positive electrode film layers with a single-layer structure includes the first positive electrode active material and the second positive electrode active material at the same time, and / or at least one layer of at least one of the positive electrode film layers with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material at the same time.

[0104] It should be noted that, when the positive electrode sheet includes two positive electrode film layers: "the positive electrode film layer has a single-layer structure or a multi-layer structure" means that the two positive electrode film layers independently have a single-layer structure or a multi-layer structure.

[0105] In some embodiments of the first aspect, a positive electrode film layer is respectively provided on the two surfaces of the positive electrode current collector, each positive electrode film layer is a single-layer structure, one positive electrode film layer includes both the first positive electrode active material and the second positive electrode active material, and the other positive electrode film layer includes the first positive electrode active material and / or the second positive electrode active material.

[0106] In some embodiments of the first aspect, a positive electrode film layer is respectively provided on the two surfaces of the positive electrode current collector, each positive electrode film layer is a multi-layer structure, and at least one layer (for example, one layer) in each positive electrode film layer includes both the first positive electrode active material and the second positive electrode active material; optionally, the remaining layers in each positive electrode film layer include the first positive electrode active material or the second positive electrode active material.

[0107] In some embodiments of the first aspect, a positive electrode film layer C and a positive electrode film layer D are respectively provided on the two surfaces of the positive electrode current collector, the positive electrode film layer C is a multi-layer structure, and the positive electrode film layer D is a single-layer structure; at least one layer of the positive electrode film layer C includes the first positive electrode active material and the second positive electrode active material at the same time, and / or the positive electrode film layer D includes the first positive electrode active material and the second positive electrode active material at the same time; optionally, when any layer of the positive electrode film layer C and the positive electrode film layer D include the first positive electrode active material and the second positive electrode active material at the same time, the remaining layers of the positive electrode film layer C include the first positive electrode active material or the second positive electrode active material; optionally, when any layer of the positive electrode film layer C includes the first positive electrode active material and the second positive electrode active material at the same time, the remaining layers of the positive electrode film layer C and the positive electrode film layer D each independently include the first positive electrode active material or the second positive electrode active material; optionally, when the positive electrode film layer D includes the first positive electrode active material and the second positive electrode active material at the same time, each layer in the positive electrode film layer C each independently includes the first positive electrode active material or the second positive electrode active material.

[0108] In some embodiments of the first aspect, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; at least one of the positive electrode film layers has a multi-layer structure, and at least one of the positive electrode film layers with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material in different layers respectively; optionally, at least one of the positive electrode film layers with a multi-layer structure includes the first positive electrode active material and the second positive electrode active material in adjacent layers respectively.

[0109] In some embodiments of the first aspect, a positive electrode film layer is respectively provided on the two surfaces of the positive electrode current collector, each positive electrode film layer is a multi-layer structure, and the two adjacent layers in each positive electrode film layer respectively include a first positive electrode active material and a second positive electrode active material.

[0110] In some embodiments of the first aspect, a positive electrode film layer E and a positive electrode film layer F are respectively arranged on the two surfaces of the positive electrode current collector, the positive electrode film layer E is a multi-layer structure, the positive electrode film layer F is a single-layer structure, and the two adjacent layers in the positive electrode film layer E respectively include a first positive electrode active material and a second positive electrode active material; optionally, the remaining layers in the positive electrode film layer E and the positive electrode film layer F each independently include the first positive electrode active material or the second positive electrode active material.

[0111] In some embodiments of the first aspect, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer A and a positive electrode film layer B respectively arranged on two surfaces of the positive electrode current collector; the positive electrode film layer A and the positive electrode film layer B each independently have a single-layer structure or a multi-layer structure; at least one layer of the positive electrode film layer A includes the first positive electrode active material, and at the same time, at least one layer of the positive electrode film layer B includes the second positive electrode active material.

[0112] In some embodiments of the first aspect, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer A and a positive electrode film layer B respectively arranged on two surfaces of the positive electrode current collector; the positive electrode film layer A and the positive electrode film layer B both have a single-layer structure; the positive electrode film layer A includes the first positive electrode active material, and at the same time, the positive electrode film layer B includes the second positive electrode active material.

[0113] The present application combines a first positive electrode active material and a second positive electrode active material. The two materials complement each other's advantages, thereby improving the energy density of the battery and enabling the battery to have excellent rate performance, kinetic performance, cycle performance, low temperature performance and safety performance.

[0114] In some embodiments of the first aspect, the mass ratio of the first positive electrode active material to the second positive electrode active material is 1:7 to 7:1, optionally 1:4 to 4:1, and further optionally 1:3 to 3:1, for example, 1:7, 1:5, 1:3, 1:2, 3:5, 1:1, 5:3, 2:1, 3:1, 5:1, and 7:1. This allows the secondary battery to have excellent rate performance, excellent cycle performance, and high-temperature stability, as well as high energy density, excellent kinetic performance, and low-temperature performance, reduce interfacial side reactions, and improve the safety of the secondary battery.

[0115] In some embodiments of the first aspect, in the first positive electrode active material, A includes one or more elements selected from the group consisting of Zn, Fe, Ti, V, Ni, Co, and Mg. Optionally, A includes at least two elements selected from the group consisting of Fe, Ti, V, Ni, Co, and Mg. Selecting the doping element within the above-mentioned range can enhance the doping effect. This can further reduce the lattice change rate, thereby inhibiting manganese dissolution and reducing the consumption of electrolyte and active lithium. Furthermore, it can further reduce surface oxygen activity and reduce interfacial side reactions between the positive electrode active material and the electrolyte, thereby improving the cycle performance and high-temperature storage performance of the secondary battery.

[0116] In some embodiments of the first aspect, x is any value within the range of -0.100 to 0.006. By selecting the value of x within this range, the kinetic performance of the battery can be improved.

[0117] In some embodiments of the first aspect, y is any value in the range of 0.001 to 0.500, and can be any value in the range of 0.1 to 0.4. By selecting the value of y within this range, the gram capacity of the first positive electrode active material and the rate performance of the battery can be improved.

[0118] In some embodiments of the first aspect, M and X each independently include one or more elements of Li and Fe.

[0119] In some embodiments of the first aspect, the ratio of y to 1-y is selected from 1:10 to 10:1, and may be 1:4 to 1:1. Here, y represents the sum of the stoichiometric ratios of the Mn-doping elements. When the above conditions are met, the energy density and cycle performance of the secondary battery fabricated from the positive electrode sheet are further improved.

[0120] In some embodiments of the first aspect, the ratio of z to 1-z is selected from 1:999 to 1:9, and may be 1:499 to 1:249. Here, z represents the sum of the stoichiometric ratios of the P-site doping elements. When the above conditions are met, the energy density and cycle performance of a secondary battery fabricated using the positive electrode sheet can be further improved.

[0121] In some embodiments of the first aspect, in the first positive electrode active material, the interplanar spacing of the phosphate in the first coating layer is 0.345-0.358 nm, and the angle of the crystal direction (111) is 24.25°-26.45°; and / or, the interplanar spacing of the pyrophosphate in the first coating layer is 0.293-0.326 nm, and the angle of the crystal direction (111) is 26.41°-32.57°.

[0122] When the interplanar spacing and the angle of the crystal orientation (111) of the phosphate and / or pyrophosphate in the first coating layer are within the above range, the impurity phase in the coating layer can be effectively avoided, thereby increasing the specific capacity of the material and improving the cycle performance and rate performance of the battery.

[0123] In some embodiments of the first aspect, in the first positive electrode active material, the coating amount of the first coating layer is greater than 0 wt % and less than or equal to 7 wt %, and can be optionally 4-5.6 wt %, based on the weight of the core.

[0124] When the coating amount of the first coating layer is within the above range, the dissolution of manganese can be further suppressed, while the transmission of lithium ions can be further promoted, the battery impedance can be reduced, and the dynamic performance of the battery can be improved.

[0125] In some embodiments of the first aspect, in the first positive electrode active material, a weight ratio of pyrophosphate to phosphate in the first coating layer is 1:3 to 3:1, and can be optionally 1:3 to 1:1.

[0126] The appropriate ratio of pyrophosphate and phosphate is conducive to fully exerting the synergistic effect of the two, inhibiting the dissolution of manganese and reducing battery impedance.

[0127] In some embodiments of the first aspect, in the first positive electrode active material, the crystallinity of the pyrophosphate and the phosphate are each independently 10% to 100%, and optionally 50% to 100%.

[0128] In the first coating layer of the lithium manganese phosphate positive electrode active material of the present application, pyrophosphate and phosphate with a certain degree of crystallinity are beneficial for maintaining the structural stability of the first coating layer and reducing lattice defects. This is beneficial for fully utilizing the pyrophosphate's effect of hindering manganese dissolution. On the other hand, it is also beneficial for the phosphate to reduce the surface impurity lithium content and the valence state of surface oxygen, thereby reducing the interfacial side reactions between the positive electrode material and the electrolyte, reducing the consumption of electrolyte, and improving the cycle performance and safety performance of the secondary battery.

[0129] In some embodiments of the first aspect, in the first positive electrode active material, the coating amount of the second coating layer is greater than 0 wt % and less than or equal to 6 wt %, and can be optionally 3-5 wt %, based on the weight of the core.

[0130] On the one hand, the carbon-containing layer as the second coating layer can play a "barrier" function, reducing the direct contact between the first positive electrode active material and the electrolyte, thereby reducing the corrosion of the electrolyte on the active material and improving the safety performance of the secondary battery at high temperatures. On the other hand, it has a strong electrical conductivity, which can reduce the internal resistance of the secondary battery, thereby improving the kinetic performance of the secondary battery. However, due to the low gram capacity of the carbon material, when the amount of the second coating layer is too large, the overall gram capacity of the positive electrode active material may be reduced. Therefore, when the coating amount of the second coating layer is within the above range, it can further improve the kinetic performance and safety performance of the secondary battery without sacrificing the gram capacity of the positive electrode active material.

[0131] In some embodiments of the first aspect, the concentration of Li / Mn antisite defects in the first positive electrode active material is less than or equal to 4%, and optionally less than or equal to 2%. In the first positive electrode active material of the present application, the Li / Mn antisite defect refers to the Li in the LiMnPO4 lattice. + and Mn 2+ The positions of Li are interchanged. + The transmission channel is a one-dimensional channel, Mn 2+ In Li + It is difficult to migrate in the transmission channel, so the antisite defect Mn 2+ Will hinder Li + By controlling the Li / Mn antisite defect concentration at a low level, the specific capacity of the material and the rate performance of the battery can be improved. In this application, the antisite defect concentration can be measured, for example, according to JIS K 0131-1996.

[0132] In some embodiments of the first aspect, the lattice change rate of the first positive electrode active material is less than or equal to 6%, and can be less than or equal to 4%. The lithium insertion and extraction process is a two-phase reaction. The interfacial stress of the two phases is determined by the lattice change rate. The smaller the lattice change rate, the smaller the interfacial stress. +Therefore, reducing the lattice change rate of the core will be beneficial to enhance the Li + transmission capability, thereby improving the rate performance of the secondary battery.

[0133] In some embodiments of the first aspect, the surface oxygen valence of the first positive electrode active material is less than or equal to -1.88, and can be optionally -1.98 to -1.88. This is because the higher the valence of oxygen in a compound, the stronger its electron-accepting ability, that is, the stronger its oxidizing property. In the first positive electrode active material of the present application, by controlling the surface valence of oxygen at a lower level, the reactivity of the surface of the positive electrode material can be reduced, and the interfacial side reactions between the positive electrode material and the electrolyte can be reduced, thereby improving the cycle performance and high-temperature storage performance of the secondary battery.

[0134] In some embodiments of the first aspect, the compaction density of the first positive electrode active material at 3 tons (T) is greater than or equal to 2.0 g / cm 3 , can be selected as greater than or equal to 2.2g / cm 3 The higher the compaction density of the first positive electrode active material, that is, the greater the weight of the active material per unit volume, the more conducive it is to improving the volume energy density of the secondary battery. In this application, the compaction density can be measured, for example, according to GB / T 24533-2009.

[0135] In some embodiments of the first aspect, the sum of the mass of the first positive electrode active material and the second positive electrode active material accounts for 88% to 98.7% of the mass of the positive electrode sheet, further enabling the secondary battery to have excellent rate performance, kinetic performance, cycle performance, and low-temperature performance, and to have a high energy density.

[0136] In some embodiments of the first aspect, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0137] In some embodiments of the first aspect, the positive electrode film layer may further comprise other positive electrode active materials for batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: an olivine-structured lithium-containing phosphate, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials; other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium nickel oxide (such as LiNiO2), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, and their modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0138] In some embodiments of the first aspect, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorinated acrylate resin.

[0139] In some embodiments of the first aspect, the positive electrode film layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0140] [Negative electrode]

[0141] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0142] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0143] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0144] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0145] In some embodiments, the negative electrode film layer may further include a binder. For example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0146] In some embodiments, the negative electrode film layer may further include a conductive agent. For example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0147] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0148] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0149] [Electrolytes]

[0150] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0151] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0152] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0153] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0154] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0155] [Isolation film]

[0156] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0157] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0158] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0159] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0160] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0161] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 5 with a square structure as an example.

[0162] In some embodiments, referring to FIG2 , the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0163] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0164] Figure 3 shows an example battery module 4. Referring to Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.

[0165] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0166] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0167] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0168] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0169] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0170] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0171] [Example]

[0172] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially. The content of each component in the embodiments of the present invention, unless otherwise specified, is based on the mass without crystal water.

[0173] The sources of raw materials involved in the preparation examples and embodiments of this application are as follows:

[0174] Example 1-1

[0175] (1) Preparation of co-doped lithium manganese phosphate core

[0176] Preparation of Fe, Co, and V co-doped manganese oxalate: 689.5 g of manganese carbonate (calculated as MnCO3, the same below), 455.2 g of ferrous carbonate (calculated as FeCO3, the same below), 4.6 g of cobalt sulfate (calculated as CoSO4, the same below), and 4.9 g of vanadium dichloride (calculated as VCl2, the same below) were thoroughly mixed in a mixer for 6 hours. The mixture was transferred to a reactor, and 5 liters of deionized water and 1260.6 g of oxalic acid dihydrate (calculated as C2H2O4.2H2O, the same below) were added. The reactor was heated to 80°C and stirred at 600 rpm for 6 hours until the reaction terminated (no bubbles were generated), resulting in a Fe, Co, V, and S co-doped manganese oxalate suspension. The suspension was then filtered, and the filter cake was dried at 120°C and then ground to obtain Fe, Co, and V co-doped manganese oxalate dihydrate particles with a median particle size (Dv50) of 100 nm.

[0177] Preparation of Fe, Co, V, and S co-doped lithium manganese phosphate: 1793.4 g of manganese oxalate dihydrate particles obtained in the previous step, 369.0 g of lithium carbonate (calculated as Li CO ), 1.6 g of 60% dilute sulfuric acid (calculated as 60% H SO ), and 1148.9 g of ammonium dihydrogen phosphate (calculated as NH H PO ) were added to 20 liters of deionized water. The mixture was stirred for 10 hours to mix uniformly to obtain a slurry. The slurry was transferred to a spray drying apparatus for spray drying and granulation at a drying temperature of 250° C. for 4 hours to obtain a powder. The powder was sintered at 700° C. for 4 hours in a protective atmosphere of nitrogen (90% by volume) and hydrogen (10% by volume) to obtain 1572.1 g of Fe, Co, V, and S co-doped lithium manganese phosphate.

[0178] (2) Preparation of lithium iron pyrophosphate and lithium iron phosphate

[0179] Preparation of lithium iron pyrophosphate powder: 4.77g lithium carbonate, 7.47g ferrous carbonate, 14.84g ammonium dihydrogen phosphate and 1.3g oxalic acid dihydrate were dissolved in 50ml deionized water. The pH of the mixture was 5, and the mixture was stirred for 2 hours to allow the reaction mixture to fully react. The reacted solution was then heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7. The suspension was filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder was sintered at 650°C in a nitrogen atmosphere for 8 hours, naturally cooled to room temperature, and then ground to obtain Li2FeP2O7 powder.

[0180] Preparation of lithium iron phosphate suspension: 11.1g lithium carbonate, 34.8g ferrous carbonate, 34.5g ammonium dihydrogen phosphate, 1.3g oxalic acid dihydrate and 74.6g sucrose (C 12 H 22 O11 The mixture was stirred for 6 hours to allow the mixture to react completely. The reaction solution was heated to 120° C. and maintained at this temperature for 6 hours to obtain a suspension containing LiFePO 4 .

[0181] (3) Coating

[0182] 1572.1g of the Fe, Co, V, and S co-doped lithium manganese phosphate and 15.72g of the lithium iron pyrophosphate (Li2FeP2O7) powder were added to the lithium iron phosphate (LiFePO4) suspension prepared in the previous step. After stirring and mixing, the mixture was transferred to a vacuum oven and dried at 150°C for 6 hours. The resulting product was then dispersed by sand milling. After dispersion, the resulting product was sintered at 700°C in a nitrogen atmosphere for 6 hours to obtain the target product, a double-layer-coated lithium manganese phosphate.

[0183] Examples 1-2 to 1-6

[0184] In the preparation process of the co-doped lithium manganese phosphate core, the preparation conditions of the lithium manganese phosphate core in Examples 1-2 to 1-6 are the same as those in Example 1-1, except that vanadium dichloride and cobalt sulfate are not used, and 463.4 g of ferrous carbonate, 1.6 g of 60% dilute sulfuric acid, 1148.9 g of ammonium dihydrogen phosphate and 369.0 g of lithium carbonate are used.

[0185] In addition, in the preparation process of lithium iron pyrophosphate and lithium iron phosphate and the process of coating the first coating layer and the second coating layer, except that the raw materials used are adjusted according to the ratio of the coating amount shown in Table 1 to the coating amount corresponding to Example 1-1, so that the amount of Li2FeP2O7 / LiFePO4 in Examples 1-2 to 1-6 is 12.6g / 37.7g, 15.7g / 47.1g, 18.8g / 56.5g, 22.0 / 66.0g and 25.1g / 75.4g respectively, and the amount of sucrose in Examples 1-2 to 1-6 is 37.3g, other conditions are the same as Example 1-1.

[0186] Examples 1-7 to 1-10

[0187] The conditions of Examples 1-7 to 1-10 are the same as those of Example 1-3, except that the amounts of sucrose used are 74.6 g, 149.1 g, 186.4 g and 223.7 g, respectively, so that the corresponding coating amounts of the carbon layer as the second coating layer are 31.4 g, 62.9 g, 78.6 g and 94.3 g, respectively.

[0188] Examples 1-11 to 1-14

[0189] The conditions of Examples 1-11 to 1-14 are the same as those of Example 1-7, except that during the preparation of lithium iron pyrophosphate and lithium iron phosphate, the amounts of various raw materials are adjusted accordingly according to the coating amounts shown in Table 1 so that the amounts of Li2FeP2O7 / LiFePO4 are 23.6g / 39.3g, 31.4g / 31.4g, 39.3g / 23.6g and 47.2g / 15.7g, respectively.

[0190] Examples 1-15

[0191] The conditions of Example 1-15 were the same as those of Example 1-14, except that 492.80 g of ZnCO 3 was used instead of ferrous carbonate during the preparation of the co-doped lithium manganese phosphate core.

[0192] Examples 1-16 to 1-18

[0193] The conditions of Examples 1-17 to 1-19 are the same as those of Example 1-7, except that 466.4 g of NiCO 3 , 5.0 g of zinc carbonate and 7.2 g of titanium sulfate are used instead of ferrous carbonate in the preparation process of the co-doped lithium manganese phosphate core in Example 1-16, 455.2 g of ferrous carbonate and 8.5 g of vanadium dichloride are used in the preparation process of the co-doped lithium manganese phosphate core in Example 1-17, and 455.2 g of ferrous carbonate, 4.9 g of vanadium dichloride and 2.5 g of magnesium carbonate are used in the preparation process of the co-doped lithium manganese phosphate core in Example 1-18.

[0194] Examples 1-19 to 1-20

[0195] The conditions of Examples 1-19 to 1-20 were the same as those of Example 1-18, except that 369.4 g of lithium carbonate and 1.05 g of 60% dilute nitric acid were used instead of dilute sulfuric acid during the preparation of the co-doped lithium manganese phosphate core in Example 1-19, and 369.7 g of lithium carbonate and 0.78 g of silicic acid were used instead of dilute sulfuric acid during the preparation of the co-doped lithium manganese phosphate core in Example 1-20.

[0196] Examples 1-21 to 1-22

[0197] The conditions of Examples 1-21 to 1-22 are the same as those of Example 1-20, except that 632.0 g of manganese carbonate, 463.30 g of ferrous carbonate, 30.5 g of vanadium dichloride, 21.0 g of magnesium carbonate and 0.78 g of silicic acid are used in the preparation process of the co-doped lithium manganese phosphate core in Example 1-21; and 746.9 g of manganese carbonate, 289.6 g of ferrous carbonate, 60.9 g of vanadium dichloride, 42.1 g of magnesium carbonate and 0.78 g of silicic acid are used in the preparation process of the co-doped lithium manganese phosphate core in Example 1-22.

[0198] Examples 1-23 to 1-24

[0199] The conditions of Examples 1-23 to 1-24 are the same as those of Example 1-22, except that 804.6 g of manganese carbonate, 231.7 g of ferrous carbonate, 1156.2 g of ammonium dihydrogen phosphate, 1.2 g of boric acid (mass fraction 99.5%) and 370.8 g of lithium carbonate are used in the preparation process of the co-doped lithium manganese phosphate core in Example 1-23; and 862.1 g of manganese carbonate, 173.8 g of ferrous carbonate, 1155.1 g of ammonium dihydrogen phosphate, 1.86 g of boric acid (mass fraction 99.5%) and 371.6 g of lithium carbonate are used in the preparation process of the co-doped lithium manganese phosphate core in Example 1-24.

[0200] Examples 1-25

[0201] The conditions of Example 1-25 were the same as those of Example 1-20, except that 370.1 g of lithium carbonate, 1.56 g of silicic acid, and 1147.7 g of ammonium dihydrogen phosphate were used in the preparation of the co-doped lithium manganese phosphate core of Example 1-25.

[0202] Examples 1-26

[0203] The conditions of Example 1-26 are the same as those of Example 1-20, except that 368.3 g of lithium carbonate, 4.9 g of 60% by mass dilute sulfuric acid, 919.6 g of manganese carbonate, 224.8 g of ferrous carbonate, 3.7 g of vanadium dichloride, 2.5 g of magnesium carbonate, and 1146.8 g of ammonium dihydrogen phosphate are used in the preparation process of the co-doped lithium manganese phosphate core in Example 1-26.

[0204] Examples 1-27

[0205] The conditions of Example 1-27 were the same as those of Example 1-20, except that 367.9 g of lithium carbonate, 6.5 g of 60% dilute sulfuric acid, and 1145.4 g of ammonium dihydrogen phosphate were used in the preparation of the co-doped lithium manganese phosphate core.

[0206] Examples 1-28 to 1-33

[0207] The conditions of Examples 1-28 to 1-33 are the same as those of Example 1-20, except that 1034.5 g of manganese carbonate, 108.9 g of ferrous carbonate, 3.7 g of vanadium dichloride and 2.5 g of magnesium carbonate are used in the preparation process of the co-doped lithium manganese phosphate core, the amounts of lithium carbonate used are 367.6 g, 367.2 g, 366.8 g, 366.4 g, 366.0 g and 332.4 g, respectively, the amounts of ammonium dihydrogen phosphate used are 1144.5 g, 1143.4 g, 1142.2 g, 1141.1 g, 1139.9 g and 1138.8 g, respectively, and the amounts of 60% dilute sulfuric acid used are 8.2 g, 9.8 g, 11.4 g, 13.1 g, 14.7 g and 16.3 g, respectively.

[0208] Examples 1-34

[0209] Lithium manganate LiMn2O4 is used as the positive electrode active material.

[0210] Examples 1-35

[0211] The positive electrode active materials of Example 1-1 and Example 1-34 were mixed at a mass ratio of 1:1.

[0212] Examples 1-36

[0213] The positive electrode active materials of Example 1-7 and Example 1-34 were mixed at a mass ratio of 1:1.

[0214] Examples 1-37

[0215] The positive electrode active materials of Example 1-11 and Example 1-34 were mixed at a mass ratio of 1:1.

[0216] Examples 1-38

[0217] The positive electrode active materials of Example 1-16 and Example 1-34 were mixed at a mass ratio of 1:1.

[0218] Examples 1-39

[0219] The positive electrode active materials of Example 1-19 and Example 1-34 were mixed at a mass ratio of 1:1.

[0220] Examples 1-40

[0221] The positive electrode active materials of Example 1-21 and Example 1-34 were mixed at a mass ratio of 1:1.

[0222] Example 1-41

[0223] The positive electrode active materials of Example 1-23 and Example 1-34 were mixed at a mass ratio of 1:1.

[0224] Examples 1-42

[0225] The positive electrode active materials of Example 1-25 and Example 1-34 were mixed at a mass ratio of 1:1.

[0226] Examples 1-43

[0227] The positive electrode active materials of Example 1-26 and Example 1-34 were mixed at a mass ratio of 1:1.

[0228] Examples 1-44

[0229] The positive electrode active materials of Example 1-27 and Example 1-34 were mixed at a mass ratio of 1:1.

[0230] Examples 1-45

[0231] The positive electrode active materials of Example 1-28 and Example 1-34 were mixed at a mass ratio of 1:1.

[0232] Example 2-1

[0233] Except that in the preparation process of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step is 550°C and the sintering time is 1 hour to control the crystallinity of Li2FeP2O7 to 30%, and in the preparation process of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step is 650°C and the sintering time is 2 hours to control the crystallinity of LiFePO4 to 30%, other conditions are the same as Example 1-1.

[0234] Example 2-2

[0235] Except that in the preparation process of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step is 550°C and the sintering time is 2 hours to control the crystallinity of Li2FeP2O7 to 50%, and in the preparation process of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step is 650°C and the sintering time is 3 hours to control the crystallinity of LiFePO4 to 50%, other conditions are the same as Example 1-1.

[0236] Example 2-3

[0237] Except that in the preparation process of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step is 600°C and the sintering time is 3 hours to control the crystallinity of Li2FeP2O7 to 70%, and in the preparation process of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step is 650°C and the sintering time is 4 hours to control the crystallinity of LiFePO4 to 70%, other conditions are the same as Example 1-1.

[0238] Examples 2-4

[0239] Except that in the preparation process of lithium iron pyrophosphate (Li2FeP2O7), the sintering temperature in the powder sintering step is 650°C and the sintering time is 4 hours to control the crystallinity of Li2FeP2O7 to 100%, and in the preparation process of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step is 700°C and the sintering time is 6 hours to control the crystallinity of LiFePO4 to 100%, other conditions are the same as Example 1-1.

[0240] Examples 3-1 to 3-12

[0241] Except for the process of preparing Fe, Co and V co-doped manganese oxalate particles, the heating temperature / stirring time in the reactor of Example 3-1 is 60°C / 120 minutes; the heating temperature / stirring time in the reactor of Example 3-2 is 70°C / 120 minutes; the heating temperature / stirring time in the reactor of Example 3-3 is 80°C / 120 minutes; the heating temperature / stirring time in the reactor of Example 3-4 is 90°C / 120 minutes; the heating temperature / stirring time in the reactor of Example 3-5 is 100°C / 120 minutes; the heating temperature / stirring time in the reactor of Example 3-6 is 110°C / 120 minutes; -7 The heating temperature / stirring time in the reactor of Example 3-8 are 120°C / 120 minutes respectively; the heating temperature / stirring time in the reactor of Example 3-8 are 130°C / 120 minutes respectively; the heating temperature / stirring time in the reactor of Example 3-9 are 100°C / 60 minutes respectively; the heating temperature / stirring time in the reactor of Example 3-10 are 100°C / 90 minutes respectively; the heating temperature / stirring time in the reactor of Example 3-11 are 100°C / 150 minutes respectively; and the heating temperature / stirring time in the reactor of Example 3-12 are 100°C / 180 minutes respectively. Other conditions of Examples 3-1 to 3-12 are the same as those of Example 1-1.

[0242] Examples 4-1 to 4-4:

[0243] Except that the drying temperature / drying time in the drying step during the preparation of lithium iron pyrophosphate (Li2FeP2O7) are 100℃ / 4h, 150℃ / 6h, 200℃ / 6h and 200℃ / 6h respectively; and the sintering temperature and sintering time in the sintering step during the preparation of lithium iron pyrophosphate (Li2FeP2O7) are 700℃ / 6h, 700℃ / 6h, 700℃ / 6h and 600℃ / 6h respectively, other conditions are the same as Examples 1-7.

[0244] Examples 4-5 to 4-7:

[0245] Except that the drying temperature / drying time in the drying step during the coating process are 150℃ / 6h, 150℃ / 6h and 150℃ / 6h respectively; and the sintering temperature and sintering time in the sintering step during the coating process are 600℃ / 4h, 600℃ / 6h and 800℃ / 8h respectively, other conditions are the same as Examples 1-12.

[0246] Comparative Example 1

[0247] Preparation of manganese oxalate: 1149.3 g of manganese carbonate was added to a reactor, along with 5 liters of deionized water and 1260.6 g of oxalic acid dihydrate (calculated as C₂H₂O₄·2H₂O, the same below). The reactor was heated to 80°C and stirred at 600 rpm for 6 hours, until the reaction ceased (no bubbles were generated), to obtain a manganese oxalate suspension. The suspension was then filtered, and the filter cake was dried at 120°C and ground to obtain manganese oxalate dihydrate particles with a median particle size (Dv50) of 100 nm.

[0248] Preparation of carbon-coated lithium manganese phosphate: 1789.6 g of the above-obtained dihydrate manganese oxalate particles, 369.4 g of lithium carbonate (calculated as Li2CO3, the same below), 1150.1 g of ammonium dihydrogen phosphate (calculated as NH4H2PO4, the same below) and 31 g of sucrose (calculated as C 12 H 22 O 11 The slurry was then transferred to a spray dryer for spray drying and granulation at 250°C for 4 hours to obtain a powder. The powder was then sintered at 700°C for 4 hours in a protective atmosphere of nitrogen (90% by volume) and hydrogen (10% by volume) to obtain carbon-coated lithium manganese phosphate.

[0249] Comparative Example 2

[0250] Except for using 689.5 g of manganese carbonate and additionally adding 463.3 g of ferrous carbonate, other conditions of Comparative Example 2 are the same as those of Comparative Example 1.

[0251] Comparative Example 3

[0252] Except for using 1148.9 g of ammonium dihydrogen phosphate and 369.0 g of lithium carbonate, and additionally adding 1.6 g of 60% strength dilute sulfuric acid, other conditions of Comparative Example 3 are the same as those of Comparative Example 1.

[0253] Comparative Example 4

[0254] Except for using 689.5 g of manganese carbonate, 1148.9 g of ammonium dihydrogen phosphate and 369.0 g of lithium carbonate, and additionally adding 463.3 g of ferrous carbonate and 1.6 g of 60% concentrated dilute sulfuric acid, other conditions of Comparative Example 4 are the same as those of Comparative Example 1.

[0255] Comparative Example 5

[0256] In addition, the following steps were added: When preparing lithium iron pyrophosphate powder, 9.52g of lithium carbonate, 29.9g of ferrous carbonate, 29.6g of ammonium dihydrogen phosphate, and 32.5g of oxalic acid dihydrate were dissolved in 50ml of deionized water. The pH of the mixture was 5, and the reaction mixture was stirred for 2 hours to allow the reaction mixture to fully react. The reacted solution was then heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7. The suspension was filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder was sintered at 500°C under a nitrogen atmosphere for 4 hours, naturally cooled to room temperature, and then ground. The crystallinity of Li2FeP2O7 was controlled to be 5%. When preparing the carbon-coated material, the amount of Li2FeP2O7 used was 62.8g. The other conditions of Comparative Example 5 were the same as those of Comparative Example 4.

[0257] Comparative Example 6

[0258] In addition, the following steps were added: when preparing a lithium iron phosphate suspension, 14.7 g of lithium carbonate, 46.1 g of ferrous carbonate, 45.8 g of ammonium dihydrogen phosphate and 50.2 g of oxalic acid dihydrate were dissolved in 500 ml of deionized water, and then stirred for 6 hours to allow the mixture to fully react. The reacted solution was then heated to 120° C. and maintained at this temperature for 6 hours to obtain a suspension containing LiFePO4. In the preparation process of lithium iron phosphate (LiFePO4), the sintering temperature in the coating sintering step was 600° C. and the sintering time was 4 hours to control the crystallinity of LiFePO4 to 8%. When preparing the carbon-coated material, the amount of LiFePO4 used was 62.8 g. The other conditions of Comparative Example 6 were the same as those of Comparative Example 4.

[0259] Comparative Example 7

[0260] Preparation of lithium iron pyrophosphate powder: Dissolve 2.38g of lithium carbonate, 7.5g of ferrous carbonate, 7.4g of ammonium dihydrogen phosphate and 8.1g of oxalic acid dihydrate in 50ml of deionized water. The pH of the mixture is 5, and the reaction mixture is stirred for 2 hours to allow the reaction mixture to fully react. The reacted solution is then heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7. The suspension is filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder is sintered at 500°C in a nitrogen atmosphere for 4 hours, naturally cooled to room temperature, and then ground to control the crystallinity of Li2FeP2O7 to 5%.

[0261] Preparation of lithium iron phosphate suspension: 11.1g lithium carbonate, 34.7g ferrous carbonate, 34.4g ammonium dihydrogen phosphate, 37.7g oxalic acid dihydrate and 37.3g sucrose (C 12 H 22 O 11 The reaction mixture was heated to 120°C and maintained at this temperature for 6 hours to obtain a suspension containing LiFePO4.

[0262] 15.7 g of the obtained lithium iron pyrophosphate powder was added to the above-mentioned lithium iron phosphate (LiFePO4) and sucrose suspension. During the preparation process, the sintering temperature in the coating sintering step was 600°C, and the sintering time was 4 hours to control the crystallinity of LiFePO4 to 8%. The other conditions of Comparative Example 7 were the same as those of Comparative Example 4, and amorphous lithium iron pyrophosphate, amorphous lithium iron phosphate, and carbon-coated positive electrode active materials were obtained.

[0263] Comparative Examples 8-11

[0264] Except that the drying temperature / drying time in the drying step during the preparation of lithium iron pyrophosphate (Li2FeP2O7) are 80°C / 3h, 80°C / 3h, and 80°C / 3h in Comparative Examples 8-10, respectively; the sintering temperature and sintering time in the sintering step during the preparation of lithium iron pyrophosphate (Li2FeP2O7) are 400°C / 3h, 400°C / 3h, and 350°C / 2h in Comparative Examples 8-10, respectively; the drying temperature / drying time in the drying step during the preparation of lithium iron phosphate (LiFePO4) in Comparative Example 11 is 80°C / 3h; and the amounts of Li2FeP2O7 / LiFePO4 in Comparative Examples 8-11 are 47.2g / 15.7g, 15.7g / 47.2g, 62.8g / 0g, and 0g / 62.8g, respectively, other conditions are the same as in Examples 1-7.

[0265] The positive electrode active material prepared above, the conductive agent superconducting carbon black (Super-P), and the binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) in a weight ratio of 92:2.5:5.5, and stirred and mixed evenly to obtain a slurry of the positive electrode active material with a solid content of 60% w / w.

[0266] Comparative Example 12

[0267] The positive electrode active materials of Comparative Example 1 and Examples 1-34 were mixed at a mass ratio of 1:1.

[0268] Comparative Example 13

[0269] The positive electrode active materials of Comparative Example 2 and Examples 1-34 were mixed at a mass ratio of 1:1.

[0270] Comparative Example 14

[0271] The positive electrode active materials of Comparative Example 3 and Examples 1-34 were mixed at a mass ratio of 1:1.

[0272] Comparative Example 15

[0273] The positive electrode active materials of Comparative Example 4 and Examples 1-34 were mixed at a mass ratio of 1:1.

[0274] Comparative Example 16

[0275] The positive electrode active materials of Comparative Example 5 and Examples 1-34 were mixed at a mass ratio of 1:1.

[0276] Comparative Example 17

[0277] The positive electrode active materials of Comparative Example 6 and Examples 1-34 were mixed at a mass ratio of 1:1.

[0278] Comparative Example 18

[0279] The positive electrode active materials of Comparative Example 7 and Examples 1-34 were mixed at a mass ratio of 1:1.

[0280] Preparation of positive electrode

[0281] Example 5-1

[0282] The slurry of the positive electrode active material of Example 1-1 was prepared at 0.019 g / cm 2 The coating amount is evenly coated on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P1.

[0283] Example 5-2

[0284] The slurry of the positive electrode active material of Example 1-34 was prepared at 0.019 g / cm 2 The coating amount is evenly coated on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P2.

[0285] Example 5-3

[0286] The slurry of the positive electrode active material of Example 1-1 was prepared at 0.019 g / cm 2 The coating amount was evenly coated on one side of the aluminum foil, and the slurry of the positive electrode active material of Example 1-34 was coated at 0.019 g / cm 2The coating amount is evenly coated on the other side of the aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P3.

[0287] Example 5-4

[0288] The slurry of the positive electrode active material of Example 1-35 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as Example 5-3 to obtain the positive electrode sheet P4.

[0289] Example 5-5

[0290] The slurry of the positive electrode active material of Example 1-1 was prepared at 0.019 g / cm 2 The coating amount was evenly coated on one side of the aluminum foil, and the slurry of the positive electrode active material of Example 1-35 was coated at 0.019 g / cm 2 The coating amount is evenly coated on the other side of the aluminum foil, and the rest is the same as Example 5-3 to obtain the positive electrode sheet P5.

[0291] Examples 5-6

[0292] The slurry of the positive electrode active material of Example 1-34 was prepared at 0.019 g / cm 2 The coating amount was evenly coated on one side of the aluminum foil, and the slurry of the positive electrode active material of Example 1-35 was coated at 0.019 g / cm 2 The coating amount is evenly coated on the other side of the aluminum foil, and the rest is the same as Example 5-3 to obtain the positive electrode sheet P6.

[0293] Examples 5-7

[0294] The positive electrode active material slurry of Example 1-1 and the positive electrode active material slurry of Example 1-34 were sequentially coated on both sides of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 Then, it was dried in vacuum at a high temperature of 100-120°C for 14 hours and compacted by a roller press to obtain the positive electrode sheet P7.

[0295] Examples 5-8

[0296] The slurry of the positive electrode active material of Example 1-34 and the slurry of the positive electrode active material of Example 1-1 were sequentially coated on both sides of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 , the rest is the same as in Example 5-7, and the positive electrode sheet P8 is obtained.

[0297] Examples 5-9

[0298] The positive electrode active material slurry of Example 1-1 and the positive electrode active material slurry of Example 1-35 were sequentially coated on both sides of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 , the rest is the same as in Example 5-7, and the positive electrode sheet P9 is obtained.

[0299] Examples 5-10

[0300] The slurry of the positive electrode active material of Example 1-35 and the slurry of the positive electrode active material of Example 1-1 were sequentially coated on both sides of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 , the rest is the same as in Example 5-7, and a positive electrode sheet P10 is obtained.

[0301] Examples 5-11

[0302] The slurry of the positive electrode active material of Example 1-34 and the slurry of the positive electrode active material of Example 1-35 were sequentially coated on both sides of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 , the rest is the same as in Example 5-7, and a positive electrode sheet P11 is obtained.

[0303] Examples 5-12

[0304] The slurry of the positive electrode active material of Example 1-35 and the slurry of the positive electrode active material of Example 1-34 were sequentially coated on both sides of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 , the rest is the same as in Example 5-7, and the positive electrode sheet P12 is obtained.

[0305] Examples 5-13

[0306] The positive electrode active material slurry of Example 1-1 and the positive electrode active material slurry of Example 1-34 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The positive electrode active material slurry of Example 1-1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 Then, it was dried in vacuum at a high temperature of 100-120°C for 14 hours and compacted by a roller press to obtain the positive electrode sheet P13.

[0307] Examples 5-14

[0308] The positive electrode active material slurry of Example 1-1 and the positive electrode active material slurry of Example 1-34 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-34 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2, the rest is the same as in Example 5-13, and a positive electrode sheet P14 is obtained.

[0309] Examples 5-15

[0310] The positive electrode active material slurry of Example 1-1 and the positive electrode active material slurry of Example 1-34 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-35 is evenly coated on the B side of the aluminum foil. The coating amount of the slurry is 0.020 g / cm 2 , the rest are the same as in Example 5-13, and the positive electrode sheet P15 is obtained.

[0311] Examples 5-16

[0312] The positive electrode active material slurry of Example 1-34 and the positive electrode active material slurry of Example 1-1 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The positive electrode active material slurry of Example 1-1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P16 is obtained.

[0313] Example 5-17

[0314] The positive electrode active material slurry of Example 1-34 and the positive electrode active material slurry of Example 1-1 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-34 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P17 is obtained.

[0315] Examples 5-18

[0316] The positive electrode active material slurry of Example 1-34 and the positive electrode active material slurry of Example 1-1 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-35 is evenly coated on the B side of the aluminum foil. The coating amount of the slurry is 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P18 is obtained.

[0317] Example 5-19

[0318] The positive electrode active material slurry of Example 1-1 and the positive electrode active material slurry of Example 1-35 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The positive electrode active material slurry of Example 1-1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest are the same as in Example 5-13, and the positive electrode sheet P19 is obtained.

[0319] Example 5-20

[0320] The positive electrode active material slurry of Example 1-1 and the positive electrode active material slurry of Example 1-35 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-34 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P20 is obtained.

[0321] Example 5-21

[0322] The positive electrode active material slurry of Example 1-1 and the positive electrode active material slurry of Example 1-35 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-35 is evenly coated on the B side of the aluminum foil. The coating amount of the slurry is 0.020 g / cm 2 , the rest are the same as in Example 5-13, and a positive electrode sheet P21 is obtained.

[0323] Example 5-22

[0324] The slurry of the positive electrode active material of Example 1-35 and the slurry of the positive electrode active material of Example 1-1 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The positive electrode active material slurry of Example 1-1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P22 is obtained.

[0325] Example 5-23

[0326] The slurry of the positive electrode active material of Example 1-35 and the slurry of the positive electrode active material of Example 1-1 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-34 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2, the rest are the same as in Example 5-13, and a positive electrode sheet P23 is obtained.

[0327] Example 5-24

[0328] The slurry of the positive electrode active material of Example 1-35 and the slurry of the positive electrode active material of Example 1-1 were sequentially coated on the A side of the aluminum foil, with the coating amount of each layer of slurry being 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-35 is evenly coated on the B side of the aluminum foil. The coating amount of the slurry is 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P24 is obtained.

[0329] Example 5-25

[0330] The slurry of the positive electrode active material of Example 1-34 and the slurry of the positive electrode active material of Example 1-35 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The positive electrode active material slurry of Example 1-1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P25 is obtained.

[0331] Examples 5-26

[0332] The slurry of the positive electrode active material of Example 1-34 and the slurry of the positive electrode active material of Example 1-35 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-34 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P26 is obtained.

[0333] Example 5-27

[0334] The slurry of the positive electrode active material of Example 1-34 and the slurry of the positive electrode active material of Example 1-35 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-35 is evenly coated on the B side of the aluminum foil. The coating amount of the slurry is 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P27 is obtained.

[0335] Example 5-28

[0336] The slurry of the positive electrode active material of Example 1-35 and the slurry of the positive electrode active material of Example 1-34 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The positive electrode active material slurry of Example 1-1 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P28 is obtained.

[0337] Example 5-29

[0338] The slurry of the positive electrode active material of Example 1-35 and the slurry of the positive electrode active material of Example 1-34 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-34 was evenly coated on the B side of the aluminum foil. The coating amount of the slurry was 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P29 is obtained.

[0339] Example 5-30

[0340] The slurry of the positive electrode active material of Example 1-35 and the slurry of the positive electrode active material of Example 1-34 were sequentially coated on the A side of the aluminum foil, and the coating amount of each layer of slurry was 0.010 g / cm 2 The slurry of the positive electrode active material of Example 1-35 is evenly coated on the B side of the aluminum foil. The coating amount of the slurry is 0.020 g / cm 2 , the rest is the same as in Example 5-13, and a positive electrode sheet P30 is obtained.

[0341] Example 5-31

[0342] The slurry of the positive electrode active material of Example 1-36 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P31.

[0343] Example 5-32

[0344] The slurry of the positive electrode active material of Example 1-37 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P32.

[0345] Example 5-33

[0346] The slurry of the positive electrode active material of Example 1-38 was prepared at 0.019 g / cm 2The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P33.

[0347] Example 5-34

[0348] The slurry of the positive electrode active material of Example 1-39 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P34.

[0349] Example 5-35

[0350] The slurry of the positive electrode active material of Example 1-40 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P35.

[0351] Example 5-36

[0352] The slurry of the positive electrode active material of Example 1-41 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, vacuum dried at a high temperature of 100-120°C for 14 hours, and compacted by a roller press to obtain the positive electrode sheet P36.

[0353] Example 5-37

[0354] The slurry of the positive electrode active material of Example 1-42 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as Example 5-3 to obtain the positive electrode sheet P37.

[0355] Example 5-38

[0356] The slurry of the positive electrode active material of Example 1-43 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as Example 5-3 to obtain the positive electrode sheet P38.

[0357] Example 5-39

[0358] The slurry of the positive electrode active material of Example 1-44 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as Example 5-3 to obtain the positive electrode sheet P39.

[0359] Example 5-40

[0360] The slurry of the positive electrode active material of Example 1-45 was prepared at 0.019 g / cm 2 The coating amount is evenly applied on both sides of the current collector aluminum foil, and the rest is the same as Example 5-3 to obtain a positive electrode sheet P40.

[0361] Positive electrode sheets P41 to P57 were manufactured by referring to the method of Examples 5-40, and the different parameters are shown in Table 1.

[0362] Preparation of negative electrode sheet

[0363] The negative electrode active material artificial graphite, the conductive agent superconducting carbon black (Super-P), the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC-Na) were dissolved in deionized water in a mass ratio of 95%:1.5%:1.8%:1.7%, and stirred thoroughly to obtain a negative electrode slurry with a viscosity of 3000 mPa.s and a solid content of 52%. The negative electrode slurry was coated on a 6 μm negative electrode current collector copper foil, and then baked at 100°C for 4 hours to dry it, and roller pressed to obtain a compaction density of 1.75 g / cm 3 The negative electrode.

[0364] Isolation film

[0365] Made of polypropylene film.

[0366] Preparation of electrolyte

[0367] Ethylene carbonate, dimethyl carbonate, and 1,2-propylene glycol carbonate were mixed in a volume ratio of 1:1:1, and LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte solution. The concentration of LiPF6 in the electrolyte solution was 1 mol / L.

[0368] Preparation of full batteries

[0369] The above-mentioned positive electrode sheets are wound in the order of negative electrode sheet, separator, and positive electrode sheet to form bare cells. Aluminum and copper tabs are punched out to obtain bare cells. The copper and copper tabs, and the aluminum and aluminum tabs of the two bare cells are welded to the battery cover via adapters. After the bare cells are insulated, they are placed in an aluminum shell. The cover and the aluminum shell are welded to form a dry cell. The dry cell is baked to remove water, and then an electrolyte is injected. The battery is formed and aged to obtain a complete battery. The battery structure made with positive electrode sheets P1, P2, P3, P8, P10, P11, P12, P17, P18, P23, P24, P26, and P27 is shown in Figure 7-19.

[0370] Preparation of button cells

[0371] The prepared positive electrode active material, PVDF, and acetylene black were added to NMP at a weight ratio of 90:5:5 and stirred in a drying room to form a slurry. The slurry was coated on aluminum foil, dried, and cold pressed to form a positive electrode sheet. The coating amount was 0.2 g / cm 2 , compacted density is 2.0g / cm 3 .

[0372] A lithium sheet was used as the negative electrode, and a solution of 1 mol / L LiPF6 in ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC) in a volume ratio of 1:1:1 was used as the electrolyte. Together with the positive electrode sheet prepared above, they were assembled into a button battery (hereinafter also referred to as "button battery") in a button box.

[0373] Property testing of positive electrode active materials

[0374] 1. Determination of the chemical formula of the core and the composition of different coating layers:

[0375] The internal microstructure and surface structure of the positive electrode active material were characterized with high spatial resolution using spherical aberration electron microscopy (ACSTEM), and the core chemical formula of the positive electrode active material and the composition of the first and second coating layers were obtained by combining three-dimensional reconstruction technology.

[0376] 2. Initial gram capacity test of button battery:

[0377] At 2.5-4.3 V, the button cell prepared above was charged at 0.1 C to 4.3 V, then charged at a constant voltage at 4.3 V until the current was less than or equal to 0.05 mA, allowed to stand for 5 minutes, and then discharged at 0.1 C to 2.0 V. The discharge capacity at this time was the initial gram capacity, recorded as D0.

[0378] 3. Average discharge voltage (V) test:

[0379] The button battery prepared above was placed in a constant temperature environment of 25°C for 5 minutes, discharged to 2.5V at 0.1C, allowed to stand for 5 minutes, charged to 4.3V at 0.1C, and then charged at a constant voltage at 4.3V until the current was less than or equal to 0.05mA, and allowed to stand for 5 minutes; then discharged to 2.5V at 0.1C. The discharge capacity at this time is the initial gram capacity, recorded as D0, the discharge energy is the initial energy, recorded as E0, and the average discharge voltage V of the button battery is E0 / D0.

[0380] 4. Full battery 60℃ flatulence test:

[0381] The above-prepared full battery at 100% state of charge (SOC) was stored at 60°C. The open circuit voltage (OCV) and AC internal resistance (IMP) of the battery cell were measured before, during and after storage to monitor the SOC, and the volume of the battery cell was measured. The full battery was taken out after every 48 hours of storage, and the open circuit voltage (OCV) and internal resistance (IMP) were tested after standing for 1 hour. The volume of the battery cell was measured by the drainage method after cooling to room temperature. The drainage method is to first measure the gravity F1 of the battery cell separately using a balance that automatically converts the unit data on the dial, and then completely place the battery cell in deionized water (density is known to be 1g / cm 3 ), measure the gravity F2 of the battery cell at this time, and the buoyancy F 浮 That is F1-F2, and then according to Archimedes principle F 浮 =ρ×g×V 排 , the cell volume V = (F1-F2) / (ρ×g) is calculated.

[0382] According to the OCV and IMP test results, the batteries of all embodiments maintained an SOC of more than 99% throughout the experiment until the end of storage.

[0383] After 30 days of storage, the cell volume was measured, and the percentage increase in the cell volume after storage relative to the cell volume before storage was calculated.

[0384] Also, measure the residual capacity of the battery cell. Charge the full battery at 1C to 4.3V at 2.5-4.3V, then charge at a constant voltage at 4.3V until the current is less than or equal to 0.05mA. Let it rest for 5 minutes, and record the charge capacity at this point as the residual capacity of the battery cell.

[0385] 5. Full battery cycle performance test at 45°C:

[0386] At a constant temperature of 45°C, charge the prepared full battery at 1C to 4.3V at 2.5-4.3V. Then, charge at 4.3V at a constant voltage until the current is less than or equal to 0.05mA. Let it rest for 5 minutes, then discharge at 1C to 2.5V. Record the discharge capacity at this point as D0. Repeat the charge-discharge cycle until the discharge capacity drops to 80% of D0. Record the number of cycles the battery has completed.

[0387] 6. Lattice change rate test:

[0388] Under a constant temperature environment of 25°C, the positive electrode active material sample prepared above was placed in an XRD (model: Bruker D8 Discover), and the sample was tested at 1° / min. The test data was sorted and analyzed, and the lattice constants a0, b0, c0 and v0 at this time were calculated with reference to the standard PDF card (a0, b0 and c0 represent the lengths of various aspects of the unit cell, and v0 represents the unit cell volume, which can be directly obtained through the XRD refinement results).

[0389] The above-mentioned buckle battery preparation method is adopted to prepare the positive electrode active material sample into a buckle battery, and the buckle battery is charged at a small rate of 0.05C until the current is reduced to 0.01C. The positive electrode sheet in the buckle battery is then taken out and immersed in dimethyl carbonate (DMC) for 8 hours. It is then dried, powdered, and particles with a particle size of less than 500nm are screened out. Samples are taken and their unit cell volume v1 is calculated in the same manner as the above-mentioned test of fresh samples, and (v0-v1) / v0×100% is shown in the table as the lattice change rate (unit cell volume change rate) before and after complete deintercalation of lithium.

[0390] 7.Li / Mn antisite defect concentration test:

[0391] The XRD results from the "lattice change rate measurement method" are compared with the PDF (Powder Diffraction File) card of the standard crystal to determine the Li / Mn antisite defect concentration. Specifically, the XRD results from the "lattice change rate measurement method" are imported into the General Structural Analysis System (GSAS) software to automatically obtain a refined result, which includes the site occupancy of different atoms. The Li / Mn antisite defect concentration is then obtained by reading the refined result.

[0392] 8. Transition metal dissolution test:

[0393] After cycling at 45°C until the capacity decayed to 80%, the full battery was discharged at a rate of 0.1C to a cut-off voltage of 2.0V. The battery was then disassembled, the negative electrode sheet was taken out, and 30 unit areas (1540.25mm 2 ) discs were measured by inductively coupled plasma emission spectroscopy (ICP) using an Agilent ICP-OES730. The amounts of Fe (if Fe is doped at the Mn site of the cathode active material) and Mn were calculated based on the ICP results, thereby estimating the amount of Mn (and Fe doped at the Mn site) released after cycling. This testing was conducted in accordance with EPA-6010D-2014.

[0394] 9. Surface oxygen valence test:

[0395] Take 5g of the above-prepared positive electrode active material sample and prepare it into a buckle battery according to the above-mentioned buckle battery preparation method. The buckle battery is charged at a small rate of 0.05C until the current is reduced to 0.01C. Then take out the positive electrode sheet in the buckle battery and soak it in dimethyl carbonate (DMC) for 8 hours. Then dry it, scrape the powder, and screen out the particles with a particle size of less than 500nm. The obtained particles are measured by electron energy loss spectroscopy (EELS, the instrument model used is Talos F200S) to obtain the energy loss near-edge structure (ELNES), which reflects the state density and energy level distribution of the element. According to the state density and energy level distribution, the number of occupied electrons is calculated by integrating the valence band state density data, thereby inferring the valence state of the surface oxygen after charging.

[0396] 10. Compaction density measurement:

[0397] 5 g of the prepared positive electrode active material powder was placed in a compaction mold (U.S. CARVER mold, model 13 mm), and then the mold was placed on a compaction density instrument. A pressure of 3 T was applied, and the thickness of the powder under pressure (the thickness after pressure relief) was read on the instrument. The area of ​​the container used for the test was 1540.25 mm 2 ), and calculate the compacted density through ρ = m / v.

[0398] 11. X-ray diffraction test of the crystallinity of pyrophosphate and phosphate

[0399] Take 5g of the positive electrode active material powder prepared as above and measure the total scattering intensity by X-ray. It is the sum of the scattering intensities of the entire space matter and is only related to the intensity of the primary rays, the chemical structure, and the total number of electrons participating in the diffraction, that is, the mass, but has nothing to do with the order state of the sample; then separate the crystalline scattering and the non-crystalline scattering from the diffraction pattern, and the crystallinity is the ratio of the scattering intensity of the crystalline part to the total scattering intensity.

[0400] 12. Interplanar spacing and angle

[0401] Take 1g of each positive electrode active material powder prepared above into a 50mL test tube, and inject 10mL of 75% alcohol by mass into the test tube, then stir and disperse it thoroughly for 30 minutes, then use a clean disposable plastic pipette to take an appropriate amount of the above solution and drop it on a 300-mesh copper grid. At this time, some powder will remain on the copper grid. Transfer the copper grid and the sample to the TEM (Talos F200s G2) sample chamber for testing, obtain the original TEM test image, and save the original image format (xx.dm3).

[0402] The original image obtained from the above TEM test was opened in DigitalMicrograph software and Fourier transformed (automatically completed by the software after clicking the operation) to obtain the diffraction pattern. The distance from the diffraction spot to the center position in the diffraction pattern was measured to obtain the interplanar spacing, and the angle was calculated according to the Bragg equation.

[0403] The above results are shown in Table 2-5.

[0404] Based on Examples 1-1 to 1-33 and Comparative Example 1-4, it can be seen that the presence of the first coating layer is beneficial for reducing the Li / Mn antisite defect concentration of the obtained material and the amount of Fe and Mn dissolved after cycling, thereby increasing the battery's gram capacity after charge, and improving the battery's safety and cycle performance. When other elements are doped at the Mn and phosphorus sites, respectively, the lattice change rate, antisite defect concentration, and Fe and Mn dissolved amount of the obtained material can be significantly reduced, thereby increasing the battery's gram capacity, and improving the battery's safety and cycle performance.

[0405] Based on Examples 1-1 to 1-6, it can be seen that as the amount of the first coating layer increases from 3.2% to 6.4%, the concentration of Li / Mn antisite defects in the resulting material gradually decreases, and the amount of Fe and Mn dissolution after cycling gradually decreases. The corresponding battery's safety performance and cycling performance at 45°C are also improved, but the gram capacity per charge decreases slightly. Optionally, when the total amount of the first coating layer is 4-5.6% by weight, the overall performance of the corresponding battery is optimal.

[0406] Based on Examples 1-3 and 1-7 to 1-10, it can be seen that as the amount of the second coating layer increases from 1% to 6%, the concentration of Li / Mn antisite defects in the resulting material gradually decreases, and the amount of Fe and Mn dissolution after cycling gradually decreases. The corresponding battery's safety performance and cycling performance at 45°C are also improved, but the deducted gram capacity is slightly reduced. Optionally, when the total amount of the second coating layer is 3-5% by weight, the overall performance of the corresponding battery is optimal.

[0407] From Examples 1-11 to 1-15 and Comparative Examples 5-6, it can be seen that when Li2FeP2O7 and LiFePO4 are present in the first coating layer at the same time, especially when the weight ratio of Li2FeP2O7 and LiFePO4 is 1:3 to 3:1, and especially 1:3 to 1:1, the improvement in battery performance is more obvious.

[0408] Battery Test

[0409] The secondary batteries prepared using the positive electrode sheets P1-P57 were tested as follows:

[0410] (1) Determine the energy density and furnace temperature test results of secondary batteries according to the method in the national standard GB 38031-2020 "Safety Requirements for Power Batteries for Electric Vehicles";

[0411] (2) Needle penetration test: Charge the secondary battery to 100% SOC, pierce the battery cell with a Φ8mm steel needle at a speed of 25mm / 2, and observe for 1 hour. If no fire occurs, the test has passed;

[0412] (3) According to the national standard GBT31486-2015 “Electrical performance requirements and test methods for power batteries for electric vehicles”, the room temperature 1C rate charge capacity retention rate (vs 0.33C) and the 0.33C low temperature (-20°C) discharge capacity retention rate of the secondary battery were measured to obtain the battery cell dynamic performance data;

[0413] (4) Determine the cycle life data of secondary batteries in accordance with the national standard GBT31484-2015 “Cycle life requirements and test methods for power batteries for electric vehicles”;

[0414] The above results are shown in Table 6.

[0415] Table 6 Results of battery test

[0416] According to the above results, we can know that:

[0417] Compared with the battery using the positive electrode sheet P1, the battery using the positive electrode sheet P3-P30 has a higher room temperature rate charge capacity retention rate and low temperature discharge capacity retention rate, and successfully passed the furnace temperature test and needle puncture test; the battery using the positive electrode sheet P3-P30 has a longer cycle life than the battery using the positive electrode sheet P2.

[0418] Compared with batteries using positive electrode sheets P41-P50 containing only the first positive electrode material, batteries using positive electrode sheets P31-P40 containing the first positive electrode active material and the second positive electrode active material have higher room temperature rate charge capacity retention rate and low temperature discharge capacity retention rate; batteries using positive electrode sheets P31-P40 have longer cycle life than batteries using positive electrode sheet P2.

[0419] The above description shows that the battery made of the positive electrode sheet of the present application has higher rate performance, better dynamic performance and low-temperature performance, longer cycle life and higher safety.

[0420] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode sheet, comprising a first positive electrode active material and a second positive electrode active material; The first positive electrode active material includes a core, a first coating layer covering the core, and a second coating layer covering the first coating layer; in, The inner core comprises the compound Li 1+x Mn 1-y A y P 1-z R z O 4 , the first coating layer comprises pyrophosphate M a P 2 O 7 and phosphate X n PO 4 , the second coating layer comprises carbon element; in, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb, and Ge; R includes one or more elements of B, Si, N and S; x is any value in the range of -0.100 to 0.100; y is any value in the range of 0.001 to 0.909; z is any value in the range of 0.001 to 0.100; M and X each independently include one or more elements selected from the group consisting of Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; a is greater than 0 and less than or equal to 4; n is greater than 0 and less than or equal to 2; The second positive electrode active material includes lithium manganese oxide.

2. The positive electrode sheet according to claim 1, in, The second positive electrode active material includes LiMn 2 O 4 .

3. The positive electrode plate according to claim 1 or 2, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector; the positive electrode film layer has a single-layer structure or a multi-layer structure; at least one of the positive electrode film layers with a single-layer structure simultaneously comprises the first positive electrode active material and the second positive electrode active material, and / or at least one layer of at least one of the positive electrode film layers with a multi-layer structure simultaneously comprises the first positive electrode active material and the second positive electrode active material.

4. The positive electrode sheet according to claim 1 or 2, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector; at least one of the positive electrode film layers has a multi-layer structure, and at least one of the multi-layer positive electrode film layers comprises the first positive electrode active material and the second positive electrode active material in different layers respectively; Optionally, at least one of the positive electrode film layers having a multi-layer structure includes the first positive electrode active material and the second positive electrode active material in adjacent layers, respectively.

5. The positive electrode sheet according to claim 1 or 2, comprising a positive electrode current collector and a positive electrode film layer A and a positive electrode film layer B respectively arranged on the two surfaces of the positive electrode current collector; the positive electrode film layer A and the positive electrode film layer B each independently have a single-layer structure or a multi-layer structure; at least one layer of the positive electrode film layer A comprises the first positive electrode active material, and at the same time, at least one layer of the positive electrode film layer B comprises the second positive electrode active material.

6. The positive electrode sheet according to any one of claims 1 to 5, in, The mass ratio of the first positive electrode active material to the second positive electrode active material is 1:7 to 7:1, and can be 1:4 to 4:

1.

7. The positive electrode sheet according to any one of claims 1 to 6, in, In the first positive electrode active material, A includes one or more elements of Zn, Fe, Ti, V, Ni, Co and Mg, and optionally, A includes at least two elements of Fe, Ti, V, Ni, Co and Mg; and / or, x is any value in the range of -0.100 to 0.006; and / or, y is any value in the range of 0.001 to 0.500, and can be any value in the range of 0.1 to 0.4; and / or, M and X each independently include one or more elements of Li and Fe; and / or, The ratio of y to 1-y is 1:10 to 10:1, optionally 1:4 to 1:1; and / or, The ratio of z to 1-z is 1:999 to 1:9, and can be optionally 1:499 to 1:

249.

8. The positive electrode sheet according to any one of claims 1 to 7, in, In the first positive electrode active material, the interplanar spacing of the phosphate in the first coating layer is 0.345-0.358nm, and the angle of the crystal direction (111) is 24.25°-26.45°; and / or the interplanar spacing of the pyrophosphate in the first coating layer is 0.293-0.326nm, and the angle of the crystal direction (111) is 26.41°-32.57°.

9. The positive electrode sheet according to any one of claims 1 to 8, in, In the first positive electrode active material, the coating amount of the first coating layer is greater than 0 wt % and less than or equal to 7 wt %, and can be optionally 4-5.6 wt %, based on the weight of the core.

10. The positive electrode sheet according to any one of claims 1 to 9, in, In the first positive electrode active material, the weight ratio of the pyrophosphate to the phosphate in the first coating layer is 1:3 to 3:1, and can be optionally 1:3 to 1:

1.

11. The positive electrode sheet according to any one of claims 1 to 10, in, In the first positive electrode active material, the crystallinity of the pyrophosphate and the phosphate is independently 10% to 100%, and optionally 50% to 100%.

12. The positive electrode sheet according to any one of claims 1 to 11, in, In the first positive electrode active material, the coating amount of the second coating layer is greater than 0 wt % and less than or equal to 6 wt %, and can be optionally 3-5 wt %, based on the weight of the core.

13. The positive electrode sheet according to any one of claims 1 to 12, in, The Li / Mn antisite defect concentration of the first positive electrode active material is less than or equal to 4%, and can be less than or equal to 2%.

14. The positive electrode sheet according to any one of claims 1 to 13, in, The lattice change rate of the first positive electrode active material is less than or equal to 6%, and can be optionally less than or equal to 4%.

15. The positive electrode sheet according to any one of claims 1 to 14, in, The surface oxygen valence of the first positive electrode active material is less than or equal to -1.88, and can be -1.98 to -1.

88.

16. The positive electrode sheet according to any one of claims 1 to 15, in, The compaction density of the first positive electrode active material at 3 tons (T) is greater than or equal to 2.0 g / cm 3 , can be selected as greater than or equal to 2.2g / cm 3 .

17. The positive electrode sheet according to any one of claims 1 to 16, in, The sum of the mass of the first positive electrode active material and the second positive electrode active material accounts for 88% to 98.7% of the mass of the positive electrode sheet.

18. A battery comprising the positive electrode sheet according to any one of claims 1 to 17.

19. An electrical device comprising the battery according to claim 18.

Citation Information

Patent Citations

  • Lithium ion battery capable of quick charging

    CN104347880A

  • Positive electrode active material, positive electrode containing positive electrode active material and lithium secondary battery

    CN109888201A

  • Composite material containing lithium manganese ferric phosphate with core-shell structure and preparation method thereof

    CN110416525A

  • Positive electrode plate and lithium ion battery

    CN110660961A

  • Dual-composite modified spinel lithium manganate positive plate, preparation method thereof and lithium ion battery

    CN113054157A